Case report: A compound heterozygous mutations in ARSA associated with adult-onset metachromatic leukodystrophy - Wang, Bing-lei; Lu, Fen-lei; Sun, Yu-chen; Wang, Hui-juan (Frontiers in Neurology, 2022)
Metachromatic Leukodystrophy (MLD) is a rare autosomal recessive disease, which is caused by mutations in the arylsulfatase A (ARSA) gene. The ARSA gene is located on chromosome 22q13, containing eight exons. According to the age of onset, MLD can be divided into late infantile type, juvenile type, and adult type. Adult MLD has an insidious onset after the age of 16 years. Additionally, intellectual as well as behavioral changes, such as memory deficits or emotional instability, are commonly the first presenting symptoms. There is a study that reported an adult-onset MLD manifested cognitive impairment progressively due to compound heterozygous mutations of NM_000487: c.[185_186dupCA], p.(Asp63GlnfsTer18), and NM_000487: c.[154G>T], p.(Gly172Cys), rs74315271 in the ARSA gene, finding that the c.[154G>T], p.(Gly172Cys) is a novel missense mutation. Brain magnetic resonance imaging (MRI) revealed symmetrical demyelination of white matter. The activity of ARSA enzymatic in leukocytes decreased. Nerve conduction studies displayed that evidence of polyneuropathy was superimposed upon diffuse, uniform demyelinating, and sensorimotor polyneuropathy. Family genes revealed that each family member carried one of two heterozygous mutant genes. She has been discharged and is currently being followed up. This study found a compound heterozygous mutation in the ARSA gene associated with MLD and identified a novel missense mutation NM_000487: c.[154G>T], p.(Gly172Cys), rs74315271. This will provide a critical clue for prenatal diagnosis of the offspring in this family, and expand the mutation spectrum of MLD-related ARSA.